Effect of amino acids on antibiotic production by Aspergillus SPP. antagonistic to citrus canker pathogen - Masroor, Mohammad Khalid (1990)
Effect of amino acids on antibiotic production by Aspergillus clavatus Desmazieres, Apergillus flavus link ex Fries and Aspergillus niger Van Tieghem antagonistic to Xanthomonas campestris pv. citri (Hasse) Dye was studied. It was found that asparagine followed by glutamine, proline, alamine, glycine, isoleucine, valine, glutamic acid, arginine and peptone proved to be good sources for antibiotic production in all antagonists.
Includes bibliographical references (pages 168-169)